Mortality among birds and bats during an extreme heat event in eastern South Africa - McKechnie, Andrew E.; Rushworth, Ian A.; Myburgh, Ferdi; Cunningham, Susan J. (Austral ecology, 2021)
Heat‐related mortality events involving birds and bats are projected to occur more frequently as a result of anthropogenic global heating. Reports of mass mortalities associated with extreme heat have, over the last decade, mostly involved Australian birds and pteropodid flying‐foxes. Here, we report a mortality event involving ~110 birds and fruit bats in eastern South Africa in early November 2020 when maximum air temperatures (Tmax) reached 43–45°C and relative humidities were 21–23%. The mortalities included 47 birds of 14 species, all but three of which were passerines, and ~60 Wahlberg’s epauletted fruit bats (Epomophorus wahlbergi). This mortality event occurred on a single very hot day preceded by several cooler days (Tmax = 37–39°C at one location) and involved weather conditions similar to those associated with at least one recent flying‐fox die‐off in Australia. The disproportionately high representation of passerines among the avian mortalities supports recent predictions that songbirds are more vulnerable to lethal hyperthermia on account of the relative inefficiency of panting as an avenue of evaporative heat dissipation. As far as we are aware, this is the first documented heat‐related mortality event involving wild birds and bats in southern Africa. We report a significant mortality event involving birds and bats during extreme heat in eastern South Africa in early November 2020. Approximately 50 birds (mostly passerines) and 60 bats were found dead in northern KwaZulu‐Natal following maximum air temperatures of 43–45°C, although these likely represent only a small fraction of mortalities. Whereas similar heat‐related mortality events are regularly documented in Australia, this is first such event reported for southern Africa.